A randomized controlled trial comparing two types of retractors at caesarean delivery*. (17th November 2017) - Hardy-Fairbanks, Abbey J.; Mackenzie, Todd; McCarthy, Martin; Goldman, Marlene B.; Lauria, Michele R.
Abstract: The aim of this study was to determine if the use of a self-retaining, symmetrical retractor (OB/Mobius ® ) during caesarean delivery is associated with differences in post-operative pain experience. Consenting women undergoing caesarean delivery were randomly assigned to OB/Mobius ® versus conventional retraction instruments. Women were blinded to retractor type and filled out surgical pain surveys each post-operative day. Additional outcome variables were collected through a provider survey and chart review. Of the 154 randomised women, 144 completed the study. There was no difference in the symmetry, quality or intensity of postoperative pain based on the method of retraction. The OB/Mobius ® retractor did not confer an improvement in the quality or intensity of post-caesarean discomfort in the first three days following delivery. Nor did the groups differ in operative times, blood loss or pain medication usage. However, the retractor may offer improved visualisation and retraction in obese women. Impact statement: Use of a plastic sheath self-retaining retractor has been minimally studied in caesarean deliveries. Recently it was found that the use of such a retractor reduced wound infection, but another study in obese women did not show improved rates of infection (Hinkson et al.2016 ; Scolari Childress et al.2016 ). The study of sheath self-retaining retractors to decrease post-operative pain has not been reported previously. This study offers an investigation into a generalisable population of parturients who undergo caesarean delivery and if the primary use of a self-retaining retractor versus sole use of traditional hand-held retractors decreased post-operative pain while in the hospital. Although this study did not show an improvement in post-operative pain, provider experience reports demonstrated some improvement in visualisation, particularly in the obese population with the use of this novel retractor, thus making it an option for providers who do caesarean deliveries without an assistant and find hand-held retractors inadequate.